Developing a data-driven failure decision-making framework for sustainable urban water management projects - Kineber, Ahmed Farouk; Elshaboury, Nehal; Alhusban, Mohammad; Zayed, Tarek; Elsayed, Salah K.; Alkersh, Mohamad; Altuwaim, Ayman (Journal of Civil Engineering and Management, 2026)
Several degradation factors significantly impact the durability of water pipes in urban areas. However, limited research has comprehensively prioritized these factors to support data-driven maintenance and renewal decisions. Addressing this gap, this study identifies and ranks the failure factors affecting water pipeline infrastructure. A survey of 125 Egyptian water industry experts was conducted, and the collected data were analyzed using partial least squares-structural equation modeling as the decision-making framework. By incorporating insights from previous research and expert opinions, the research developed a robust failure decision-making model that provided significant insights into the primary factors contributing to water pipeline failures. Model analysis revealed that the “operational factor”, with an impact value of 0.543, was the most critical group of factors affecting pipeline failure. Following closely with an impact value of 0.480, was the “static factor”. Natural disasters (0.373), climate and weather conditions (0.325), and soil conditions (0.300) also contributed considerably. Following closely were “dynamic loads” (0.276), “aging and environmental factors” (0.250), and “third-party factors” (0.200), which had the least impact on the failure of the pipeline. This study has developed a novel failure decision-making model by synthesizing insights from previous studies, expert opinions, and empirical data on water pipeline failure.